Fundamentals of ophthalmic dispensing – part 17 Visual task analysis – part 3. Issue 4 (April 2021) - Black, Peter; Black, Tina Arbon
Abstract : In this third article on visual task analysis Peter Black and Tina Arbon Black look at dispensing solutions to the visual problems in the real world of work, home and leisure activities, concentrating principally on outdoor tasks including aspects of regulations and standards relating to sports, health and safety and driving.